Primary curriculum Box. CLIL (Content Language Integrated Learning) lessons and activities for younger learners + CD - Bentley, Kate (Cambridge Cambridge University press, 2009)
Thought-provoking topics include art and drama, literacy, maths, science and the environement. "Learn about" sections give you all the background information you need to teach confidently.... Make your life easy with these photocopiable lessons that are simple to use and quick to prepare !
Contents.
Keywords: Language; Learning; vocabulary; Activities; Games; English - foreign language